Pengaruh Optimism Terhadap Body Image Remaja Putri Pengguna Produk Kecantikan Di Karawang - Edytia Prameswari Aisyah; Marhisar Simatupang; Dinda Aisha (unprimdn.ac.id, 2023)
In adolescence there are physical changes, such as rapid growth and increase in height, weight, hormonal changes, sexual maturity and increased function of the brain structure. This is a problem that is still felt especially by young women because these teenagers are starting to pay attention to and take an attitude towards their body and appearance. This can be seen from the beauty and body care products from the latest brands and the emergence of beauty and body care products specifically aimed at